Hydrogen, ethanol and cellulase production from pulp and paper primary sludge by fermentation with Clostridium thermocellum. (January 2015) - Moreau, Alexandre; Montplaisir, Daniel; Sparling, Richard; Barnabé, Simon
Abstract: Pulp and paper industry primary sludge being largely composed of lignocellulosic fibres, it could be used as carbon source by bacteria having cellulolytic capability. The aim of this study was to evaluate the use of cellulose contained in this type of sludge for Clostridium thermocellum to produce ethanol, hydrogen and cellulases. In an ATCC 1191 medium containing 5 kg m −3 dry primary sludge from recycled paper mill, batch culture reached stationary phase after 2 days. All of the available cellulose was hydrolysed after 60 h of incubation, with a final pH of 5.83. Metabolites produced after 60 h of fermentation were acetate (8.50 mol m −3 ), ethanol (11.30 mol m −3 ), lactate (8.75 mol m −3 ), formate (0.27 mol m −3 ), hydrogen (11.20 mol m −3 ) and carbon dioxide (18.41 mol m −3 ). Cellulase activity was detected in the supernatant after 36 h, with a maximal activity of 0.25 U cm −3 at 72 h. Pulp and paper primary sludge appeared to be a readily usable substrate for C. thermocellum at this concentration, yielding both potential biofuels (hydrogen and ethanol) as well as active cellulases. Highlights: Recycled paper mill primary sludge at 5 kg m −3 appeared to be a suitable carbon source for fermentation with C. thermocellum One step fermentation directly from this cellulosic substrate produced ethanol (11.3 mol m −3 ) and hydrogen (11.2 mol m −3 ). Cellulase activity in supernatant was 0.25 U cm −3 and cellulose present in sludge was completely hydrolysed in 60 h.